Relationship between Maximum Tongue Pressure Value and Age, Occlusal Status, or Body Mass Index among the Community-Dwelling Elderly - Hiroki Suzuki (Medicina, 2020)
Background and objectives: In an aging society, the maintenance of the oral function of the elderly is of importance for the delay or prevention of frailty and long-term care. In the present study, we focused on the maximum tongue pressure (MTP) value and analyzed the relationship between MTP and age, occlusal status, or body mass index (BMI). Materials and Methods: This one-center observatory study was conducted using a cohort consisting of 205 community-dwelling outpatients over 65 years old. The MTP values of all subjects were measured using a commercially available tongue pressure measurement device and statistically analyzed. In addition, the correlation between MTP value and BMI was analyzed. Results: The MTP value decreased with age, especially in subjects classified as Eichner B and C. The difference in occlusal status did not show any statistically significant influence on MTP value. The correlation between BMI and MTP value was indicated in the tested groups other than an age of 65–74 and Eichner A groups. Conclusions: Although MTP value decreased with age, the difference in occlusal status did not have an impact on MTP value. The correlation between BMI and MTP value was not shown in the youngest group or a group with sufficient occlusal units. The results presented in the present study may imply that, even if MTP is low, younger age and/or better occlusal status compensate for the inferior MTP value in the cohort studied.